Parental Background, Primary to Secondary School Transitions, and Wages - Christian Dustmann (Institute for the Study of Labor (IZA), 2001)
The degree to which economic status is transmitted from one generation to the next is an important indicator for the inequality of opportunities. One crucial element of intergenerational mobility is the way parents influence the education of their children. Unlike in the UK or in the US, in Germany an important decision about which educational track to follow is made at a relatively early stage: after primary school, at around the age of ten. In this paper, we use micro data to analyse the association between parents? education and professional class and secondary track school choice and subsequent career prospects of the child. Our analysis covers the last 6 decades. We demonstrate that parents? educational background and professional class are strongly related to the secondary track school the child follows, and subsequent educational achievements. We find a slight convergence for individuals from different parental background over the last decades. We also find convergence between males and females. The relationship between parental class and children?s education translates into earnings differentials later in life.
Keywords: J31; I2; J24; 330; Education; parental background; school transitions; Bildungsniveau; Bildungsertrag; Familie; Soziale Schicht; Allgemeinbildende Schule; Absolventen; Schätzung; Deutschland